THE EFFECT OF HPP LAW KNOWLEDGE, TAX RATES, AND TAX SYSTEM EFFECTIVENESS ON TAXPAYER COMPLIANCE - Apip Apip; Kholidin Kholidin; Herry Laksito (Jurnal RAK (Riset Akuntansi Keuangan), 2024)
The purpose of this study was to ascertain how MSMEs' taxpayer compliance in Central Java was impacted by taxpayer understanding of the HPP Law, tax rates, and the efficiency of the tax system. Quantitative research methodology is employed. Using a sample of 100 respondents and a random sampling technique based on the Slovin formula, the population in this study was made up of MSME players in Central Java. Multiple Linear Regression was employed as the data analysis method. The study's findings show that tax rates and tax knowledge positively impact MSMEs' taxpayer compliance in Central Java, while the efficiency of the tax system has little bearing on taxpayer compliance. Understanding the regulations and the amount of tax rates set by the government increases taxpayer compliance behavior. The taxation system in Indonesia is based on technology and is not fully understood by MSMEs so the taxation system does not run effectively.